Organic-inorganic composite filler, its manufacturing method, and dental hardenable composition containing said organic-inorganic composite filler

By using porous organic-inorganic composite particles with an irregular shape and high inorganic content, the challenges of low mechanical strength and poor operability in dental curable compositions are addressed, resulting in enhanced mechanical strength and morphological retention.

JP7669007B2Active Publication Date: 2025-04-28TOKUYAMA DENTAL CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021069526
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-18
Filing Date
2021-04-16
Publication Date
2025-04-28
Estimated Expiration
2041-04-16

AI Technical Summary

Technical Problem

Dental curable compositions containing organic-inorganic composite fillers face challenges with low mechanical strength, poor operability, and morphological retention due to weak bonding between the matrix and the filler.

Method used

The development of porous organic-inorganic composite particles with an irregular shape and high inorganic content (80-95% by mass), which have a specific pore volume and particle size distribution, enhancing mechanical strength and operability.

Benefits of technology

The proposed solution significantly improves the mechanical strength, operability, and morphological retention of dental curable compositions, maintaining good paste properties even after long-term storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669007000001
    Figure 0007669007000001
  • Figure 0007669007000002
    Figure 0007669007000002
  • Figure 0007669007000003
    Figure 0007669007000003
Patent Text Reader

Abstract

To provide a fine porous organic inorganic composite filler that is blended with a dental curable composition and thereby can enhance mechanical strength of its curable body, which has good operability and shape retention property of a dental curable composition paste before curing over a long period of time.SOLUTION: An organic inorganic composite filler is a composite body of an organic resin component (A) composed of a cured body of a polymerizable monomer (a) and inorganic particles (B) having an average primary particle diameter of 10-1,000 nm, in which the organic inorganic composite filler is composed of an aggregate of porous organic inorganic composite particles that are composed of a composite body having a percentage content of the inorganic particles (B) of 80-95 mass%, an integrated pore volume of a pore of 1-500 nm when measured by a nitrogen adsorption method is 0.01-0.30 cm3 / g, and the individual porous organic inorganic composite particles constituting the organic inorganic composite filler is amorphous.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel organic-inorganic composite filler, a method for producing the same, and a dental hardenable composition containing the organic-inorganic composite filler. [Background technology]

[0002] Dental hardenable compositions are generally paste-like compositions containing a polymerizable monomer, a filler, and a polymerization initiator as main components, and the type, shape, particle size, and filling amount (rate) of the filler used affect the ease of use of the dental hardenable composition and the aesthetics and mechanical strength of the hardened body obtained by hardening.

[0003] For example, when a dental hardenable composition is mixed with an inorganic filler having a large particle size, the mechanical strength of the hardened body is increased, but the surface smoothness and abrasion resistance of the hardened body are decreased, making it difficult to obtain a hardened body with a glossy finish similar to that of natural teeth. On the other hand, when a fine inorganic filler having an average particle size of 1 μm or less is mixed, the surface smoothness and abrasion resistance of the hardened body can be improved, but the fine inorganic filler has a large specific surface area, so it greatly increases the viscosity. In addition, when the amount of inorganic filler is reduced, not only does the shrinkage of the hardened body increase due to polymerization shrinkage of the monomer when the dental hardenable composition is hardened, but also the mechanical strength of the hardened body is reduced.

[0004] In order to avoid such a so-called trade-off relationship, the use of an organic-inorganic composite filler has been proposed (see, for example, Patent Documents 1 and 2). The organic-inorganic composite filler is a composite filler containing fine inorganic filler in an organic resin, and by using this, it is possible to maintain the excellent surface smoothness and abrasion resistance when a fine inorganic filler is used, and further to reduce the polymerization shrinkage rate. If the amount of the organic-inorganic composite filler is too large, the paste state becomes rough and the operability of the paste deteriorates, but by using it in combination with an inorganic filler (inorganic particles) having an average particle size of 0.1 to 1 μm, the above-mentioned decrease in operability can be prevented, and a paste-like dental curable composition with excellent operability can be obtained (see Patent Document 2).

[0005] The above organic-inorganic composite filler is generally produced by polymerizing a paste-like curable composition in which a fine inorganic filler and a polymerizable monomer are kneaded in advance to obtain a cured product, and then crushing the cured product. The dental curable composition containing the organic-inorganic composite filler produced by this method has a problem that the strength of the dental curable composition is low because the bond at the interface between the matrix and the organic-inorganic composite filler is weak.

[0006] As an organic / inorganic composite filler that improves the above problems, a filler having a pore volume (wherein the pores have a diameter of 1 to 500 nm) measured by mercury intrusion porosimetry of 0.01 to 0.30 cm 3 An organic-inorganic composite filler having an aggregate gap of 1 / g has been proposed (see Patent Document 3). Patent Document 3 describes that, in a dental hardenable composition comprising such a porous organic-inorganic composite filler, a polymerizable monomer, and a polymerization initiator, by using an organic-inorganic composite filler having aggregate gaps, the polymerizable monomer of the hardenable composition permeates and hardens by capillary action, generating an anchor effect, and the organic-inorganic composite filler is held in the hardened body of the hardenable composition with a high interlocking force, thereby improving mechanical strength. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2000-80013 A [Patent Document 2] International Publication No. 2015 / 125470 Brochure [Patent Document 3] International Publication No. 2011 / 115007 Brochure Summary of the Invention [Problem to be solved by the invention]

[0008] The present inventors have studied and found that the dental hardenable composition containing the organic-inorganic composite filler having aggregated gaps obtained by the method of Patent Document 3 has a considerably high mechanical strength, and a dental hardenable composition excellent in terms of wear resistance and aesthetics can be obtained. However, when the paste properties and operability of the dental hardenable composition containing the organic-inorganic composite filler obtained by the manufacturing method described in the examples, specifically, the method of aggregating an aqueous suspension in which inorganic primary particles are dispersed by spray drying to produce an aggregate of inorganic primary particles, and impregnating the obtained inorganic aggregated particles with a polymerizable monomer containing a polymerization initiator to polymerize them, the inventors have studied in detail that the paste state before hardening may be sticky and the operability may be poor, and that the ability to maintain the formed occlusal surface shape is low when filling a molar class I cavity or the like. That is, there is room for improvement in the paste operability and shape retention of the above dental hardenable composition.

[0009] In light of the above background, an object of the present invention is to provide an organic-inorganic composite filler to be blended in a dental hardenable composition, which can increase the mechanical strength of the hardened body of the dental hardenable composition, has good operability and shape retention in a paste state before hardening, and can maintain good operability for a long period of time. [Means for solving the problem]

[0010] The present invention solves the above-mentioned problems, and a first aspect of the present invention is an aggregate of porous organic-inorganic composite particles comprising a composite of an organic resin component (A) made of a cured product of a polymerizable monomer (a) and inorganic particles (B) having an average primary particle diameter of 10 to 1000 nm, and the aggregate of porous organic-inorganic composite particles has an integrated pore volume of 1 to 500 nm pores of 0.01 to 0.30 cm as measured by a nitrogen adsorption method. 3 / g, wherein the content of the inorganic particles (B) in the porous organic-inorganic composite particles is 80 to 95 mass %, and each of the porous organic-inorganic composite particles constituting the organic-inorganic composite filler has an irregular shape. the average particle size, which is the median size in a volume-based particle size distribution of the porous organic-inorganic composite particles constituting the organic-inorganic composite filler, measured by a laser diffraction-scattering method is 5 to 100 μm, and the proportion of fine particles having a size of 5 μm or less in the particle size distribution (hereinafter also referred to as "fine particle proportion") is less than 15%. The organic-inorganic composite filler is characterized in that

[0011] In the organic-inorganic composite filler of the above embodiment (hereinafter also referred to as "organic-inorganic composite filler of the present invention"), The content of the inorganic particles (B) in the porous organic-inorganic composite particles is 82 to 93 mass %, The above flat The average particle size is 10 to 100 μm. R It is particularly preferable that each of the porous organic-inorganic composite particles constituting the organic-inorganic composite filler has an irregular shape having edges, and the cumulative pore volume is 0.03 to 0.25 cm. 3 / g. Furthermore, it is preferable that the inorganic particles (B) contain inorganic particles having X-ray contrast properties.

[0012] The second aspect of the present invention is the organic / inorganic composite of the present invention. IfA method for producing a filler, comprising the steps of: a slurrying step of mixing inorganic particles (B) having an average primary particle size of 10 to 1000 nm and a polymerizable monomer component (a) in the presence of an organic solvent such that the ratio of the mass of the inorganic particles to the total mass of the two is 80 to 95 mass % to obtain a slurry in which components insoluble in the organic solvent are uniformly dispersed; a drying step of removing the organic solvent from the slurry to obtain an agglomerated mass consisting of a mixture of the polymerizable monomer component (a) and the inorganic particles (B); The method is characterized by comprising: a curing step of polymerizing and curing component (a) to obtain an aggregate microporous body consisting of a composite of organic resin component (A) consisting of a cured product of the polymerizable monomer (a) and the inorganic particles (B); a grinding step of grinding the aggregate microporous body to form a powder; and a classification step of classifying the particles after the grinding step so that the average particle size, which is the median size in a volume-based particle size distribution, is 10 to 100 μm and the proportion of fine particles having a size of 5 μm or less in the particle size distribution (fine particle abundance ratio) is less than 15%.

[0013] In the method of the above aspect (hereinafter also referred to as "the manufacturing method of the present invention"), it is preferable that the inorganic particles (B) mixed in the slurrying step are aggregated particles of surface-treated primary particles, and the aggregated particles are disintegrated by mixing in the presence of the organic solvent. It is also preferable that the slurrying step comprises a first step of mixing inorganic particles (B) having an average primary particle size of 10 to 1000 nm with a polymerizable monomer component (a) such that the ratio of the mass of the inorganic particles to the total mass of both is 80 to 95 mass% to obtain a mixed powder consisting of a wet powder in which the polymerizable monomer component (a) is attached to the surfaces of the inorganic particles (B); and a second step of mixing the mixed powder with an organic solvent to obtain a slurry in which the insoluble component is uniformly dispersed in the organic solvent. 。

[0014] A third aspect of the present invention is a dental curable composition comprising the organic-inorganic composite filler of the present invention, a polymerizable monomer, and a polymerization initiator (hereinafter, also referred to as "dental curable composition of the present invention"). Effect of the Invention

[0015] When the organic-inorganic composite filler of the present invention is used as a filler for a dental curable composition, not only can it suppress polymerization shrinkage to a small level compared to the case where an inorganic filler is directly blended, like the dental curable composition blended with the porous organic-inorganic composite filler described in Patent Document 3, but it also improves the surface smoothness and abrasion resistance of the cured body, and further improves the mechanical strength of the cured body by hardening the polymerizable monomer that has infiltrated into the pores of the organic-inorganic composite filler.

[0016] Furthermore, when the organic-inorganic composite filler of the present invention is used, not only can the dental curable composition maintain paste properties with good operability and suppressed stickiness even after long-term storage without deteriorating the paste properties, but it can also improve shape retention when used as a dental filling material and shaped into a desired shape, such as an occlusal surface shape.

[0017] In addition, as shown in Patent Document 2, in order to improve the dry feeling of the paste that occurs when the amount of the organic-inorganic composite filler is large, it is necessary to add a specific inorganic filler. However, with the organic-inorganic composite filler of the present invention, 5 Presence ratio of fine particles of μm or less (Fine particle content) low Ino This can also prevent the paste from drying out. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The organic-inorganic composite filler disclosed in Patent Document 3 is derived from the above-mentioned manufacturing method, and the shape of each particle constituting the organic-inorganic composite filler is basically approximately spherical. The present inventors thought that if the shape of the organic-inorganic composite filler is changed from approximately spherical to an irregular shape, the paste properties could be changed, and conducted intensive research. As a result, they found that when a massive microporous body consisting of a composite of an organic resin component consisting of a hardened product of a polymerizable monomer and the inorganic primary particles is obtained and then pulverized, it is possible to maintain the excellent characteristics of the porous organic-inorganic composite filler described in Patent Document 3 while compensating for its shortcomings, and to improve the operability and shape retention of a dental curable composition (paste) containing the same, and thus completed the present invention.

[0019] The reason why the paste has good operability and shape retention is not clear, but it is presumed that the porous organic-inorganic composite particles have an irregular shape (not substantially spherical), preferably an irregular shape with edges, so that they do not become sticky and the shape retention is improved. Furthermore, the suppression of the roughness of the paste is considered to be due to the fact that the content of inorganic components in the porous organic-inorganic composite particles constituting the organic-inorganic composite filler is high, the amount of organic resin components having high affinity with the matrix monomer in the dental curable composition is small, and in addition, when the proportion of fine particles is very low, the contact area with the monomer is small, so that the absorption of the monomer by the porous organic-inorganic composite particles over time is suppressed.

[0020] The organic-inorganic composite filler of the present invention, its manufacturing method (the manufacturing method of the present invention), and the dental curable composition of the present invention will be described in detail below. In this specification, unless otherwise specified, the notation "x to y" using the numerical values ​​x and y means "x or more and y or less". In such a notation, when a unit is added only to the numerical value y, the unit is also applied to the numerical value x. In addition, in this specification, the term "(meth)acrylic" means both "acrylic" and "methacrylic". Similarly, the term "(meth)acrylate" means both "acrylate" and "methacrylate", and the term "(meth)acryloyl" means both "acryloyl" and "methacryloyl".

[0021] 1. Organic-inorganic composite filler of the present invention The organic-inorganic composite filler of the present invention is composed of an aggregate of porous organic-inorganic composite particles that are a composite of an organic resin component (A) made of a cured product of a polymerizable monomer (a) and inorganic particles (B) having an average primary particle diameter of 10 to 1000 nm, and has an integrated pore volume of pores with a diameter of 1 to 500 nm of 0.01 to 0.30 cm when measured by a nitrogen adsorption method. 3 / g, wherein the content of the inorganic particles (B) in the porous organic-inorganic composite particles is 80 to 95% by mass, and each of the porous organic-inorganic composite particles constituting the organic-inorganic composite filler has an irregular shape. the average particle size, which is the median size in a volume-based particle size distribution of the porous organic-inorganic composite particles constituting the organic-inorganic composite filler, measured by a laser diffraction-scattering method is 5 to 100 μm, and the proportion of fine particles having a size of 5 μm or less (fine particle abundance proportion) in the particle size distribution is less than 15%. It is characterized by:

[0022] The organic-inorganic composite filler of the present invention, like the porous organic-inorganic composite filler described in Patent Document 3, has the above-mentioned pore volume so that, when blended in a dental hardenable composition, the polymerizable monomer penetrates into the pores and hardens to obtain an effect of improving the mechanical strength of the hardened body. From the viewpoint of such an effect, the cumulative pore volume of the pores of 1 to 500 nm is 0.03 to 0.25 cm. 3 It is preferred that the molecular weight is / g.

[0023] In Patent Document 3, the total pore volume of pores with a pore diameter of 1 to 500 nm is measured by mercury intrusion porosimetry, but the pore volume of pores with diameters in the same range can also be measured by nitrogen adsorption, and the inventors' studies have confirmed that pores with a pore diameter of 1 to 500 nm have an extremely sharp pore distribution with a peak at about 50 nm, and that there are substantially no pores with a pore diameter of less than 1 nm that are difficult to measure by mercury intrusion porosimetry or pores with a pore diameter of more than 500 nm that are difficult to measure by nitrogen adsorption. Therefore, it has been decided to adopt the pore volume measured by the nitrogen adsorption method, which does not require the use of mercury, which requires careful handling, specifically, the pore volume obtained by calculating the pore size distribution from the isothermal adsorption curve by nitrogen adsorption using the BJH method.

[0024] The average pore size of the pores in the organic-inorganic composite filler is not particularly limited, but is preferably 3 to 300 nm, more preferably 10 to 200 nm. In the case of this average pore size range, a porous organic-inorganic composite filler having the above pore volume can be easily formed. The average pore size of the pores in the organic-inorganic composite filler is calculated from the pore volume obtained by calculating the pore size distribution by the BJH method from the isothermal adsorption curve by nitrogen adsorption, and the average pore size calculated from the specific surface area calculated by the BET method.

[0025] The content of inorganic particles (B) in the porous organic-inorganic composite particles constituting the organic-inorganic composite filler of the present invention is 80 to 95% by mass. If the content of the inorganic particles is too high, the porous organic-inorganic composite particles may become brittle. If the content of the inorganic particles is too low, the pores are not formed, and not only is the mechanical strength improvement effect due to the anchor effect when the particles are added to a dental hardenable composition not obtained, but the paste may become dry after long-term storage. From this viewpoint, the content of inorganic particles (B) in the porous organic-inorganic composite particles is preferably 82 to 93% by mass.

[0026] The shape of the porous organic-inorganic composite particles constituting the organic-inorganic composite filler of the present invention has an irregular shape. The irregular shape means that when the organic-inorganic composite filler is observed using a scanning electron microscope, the main surface is not a curved shape (a spherical shape, a nearly spherical shape, a doughnut shape, or a so-called torus shape such as a dimple shape in which a depression is formed on the surface of a particle), and is preferably an irregular shape having edges.

[0027] The average particle size of the porous organic-inorganic composite particles constituting the organic-inorganic composite filler of the present invention is preferably 5 to 100 μm, particularly 10 to 100 μm, and most preferably 10 to 70 μm, because this allows the filling rate of the filler that can be blended into the dental hardenable composition to be reduced without decreasing, and the filling rate of the filler that can be blended into the dental hardenable composition to be reduced. As a result, the mechanical strength of the cured product is reduced, and the adhesiveness of the dental hardenable composition is increased, which tends to deteriorate the operability. In particular, when the proportion of fine particles having a particle size of 5 μm or less is high, the paste tends to become rough. For this reason, the proportion of fine particles having a particle size of 5 μm or less is (Fine particle content) is based on volume 、 In particular, it is preferably less than 10% by volume. On the other hand, if the average particle size exceeds 100 μm, the flowability of the dental curable composition decreases, and the smoothness in a paste state tends to decrease. The content of inorganic particles (B) in the porous organic-inorganic composite particles constituting the organic-inorganic composite filler is preferably 80 to 90% by mass, particularly 82 to 88% by mass, because particles with an average particle size of less than 5 μm are unlikely to be generated by crushing, the removal rate when removing fine particles with a particle size of 5 μm or less by classification can be reduced, and the average particle size can be easily controlled to a range of 10 to 100 μm, particularly 10 to 70 μm.

[0028] The average particle size of the organic-inorganic composite filler means a median diameter determined based on a particle size distribution determined by a laser diffraction-scattering method. Specifically, it means a median diameter determined based on a particle size distribution determined by a laser diffraction-scattering method for a sample prepared by uniformly dispersing 0.1 g of the organic-inorganic composite filler in 10 mL of ethanol.

[0029] 1-1. Organic resin components and polymerizable monomers (a) The organic resin component (A) constituting the organic-inorganic composite filler of the present invention is obtained by polymerizing a polymerizable monomer (a).

[0030] As the polymerizable monomer, any polymerizable monomer such as radical polymerizable monomer, cationic polymerizable monomer, etc., used in conventional dental hardenable compositions can be used without any particular restrictions. Among them, it is preferable to use (meth)acrylate-based polymerizable monomers that are widely used, specifically, acidic group-containing (meth)acrylate-based polymerizable monomers, hydroxyl group-containing (meth)acrylate-based polymerizable monomers, monofunctional and polyfunctional (meth)acrylate-based polymerizable monomers that do not have these substituents, etc.

[0031] Examples of (meth)acrylate polymerizable monomers that can be suitably used include the following: That is, examples of acidic group-containing (meth)acrylate polymerizable monomers include (meth)acrylic acid, N-(meth)acryloyl-p-aminobenzoic acid, 2-(meth)acryloyloxybenzoic acid, 2-(meth)acryloyloxyethyl phenyl hydrogen phosphate, 2-(meth)acryloyloxyethyl phosphonic acid, etc. Examples of the hydroxyl group-containing (meth)acrylate polymerizable monomer include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 2,2-bis[(3-methacryloyloxy-2-hydroxypropyloxy)phenyl]propane, 2,2-bis[4-(4-methacryloyloxy)-3-hydroxybutoxyphenyl]propane, 2,2-bis[4-(4-methacryloyloxy)-3-hydroxybutoxyphenyl]propane, and the like. Furthermore, examples of the monofunctional and polyfunctional (meth)acrylate polymerizable monomers not having the above-mentioned substituents include methyl (meth)acrylate, ethyl (meth)acrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, neopentyl glycol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, 1,6-bis(methacrylethyloxycarbonylamino)trimethylhexane, and the like.

[0032] Among these polymerizable monomers, bifunctional or higher polymerizable monomers, more preferably bifunctional to tetrafunctional polymerizable monomers, are preferred because of their high polymerizability and the particularly high mechanical strength of the cured product, etc. These polymerizable monomers may be used alone or in combination.

[0033] When the organic-inorganic composite filler of the present invention is used as a filler for a dental curable composition, the polymerizable monomer is preferably selected so that the difference between the refractive index of the polymer and the refractive index of the inorganic primary particles is 0.1 or less. By selecting such a polymerizable monomer, sufficient transparency can be imparted to the obtained organic-inorganic composite filler. Furthermore, when the obtained organic-inorganic composite filler is used in a dental curable composition, it is preferable to select such that the difference in refractive index between the organic-inorganic composite filler and the polymer of the polymerizable monomer constituting the dental curable composition is 0.1 or less. By selecting the monomer in this way, a transparent cured product of the dental curable composition can be obtained.

[0034] 1-2.Inorganic particles (B) The inorganic particles constituting the organic-inorganic composite filler have an average primary particle size of 10 to 1000 nm, preferably 40 to 800 nm, and more preferably 50 to 600 nm. If the average primary particle size of the inorganic particles is less than 10 nm, it becomes difficult to form pores in the organic-inorganic composite particles.

[0035] On the other hand, when inorganic particles having an average primary particle size of more than 1000 nm are used in a dental hardenable composition, the polishability of the resulting hardened body decreases, making it difficult to obtain a hardened body with a smooth surface.

[0036] In addition, the shape of the inorganic particles is not particularly limited, and spherical, approximately spherical, or irregularly shaped particles can be used. From the viewpoint of excellent abrasion resistance and surface smoothness, and of being able to impart uniform pores to the organic-inorganic composite particles, spherical or approximately spherical shapes are preferred. Note that the approximately spherical shape refers to an average uniformity of 0.6 or more. The average uniformity is preferably 0.7 or more, and particularly preferably 0.8 or more.

[0037] In the present invention, the average primary particle diameter of inorganic particles is measured using a scanning or transmission electron microscope. Specifically, the image of the inorganic particles is analyzed to determine the equivalent circle diameter (diameter of a circle having the same area as the target particle). The electron microscope image is one in which the contrast between light and dark is clear and the outline of the particles can be distinguished.

[0038] Image analysis is performed using image analysis software capable of measuring at least the particle area, maximum length, and minimum width. The primary particle diameter (circle equivalent diameter), maximum length, and minimum width of the particles are determined for 30 or more randomly selected inorganic primary particles using the above method, and the average particle diameter and average uniformity of the inorganic primary particles are calculated using the following formulas.

[0039]

number

[0040]

number

[0041] In the above formula, the number of particles is defined as (n), the maximum length of the i-th particle is defined as the major axis (Li), and the diameter perpendicular to this major axis is defined as the minimum width (Bi).

[0042] The material of the inorganic particles is not particularly limited, and those used as fillers in conventional dental hardenable compositions can be used without any particular limitation. Specifically, inorganic oxides such as amorphous silica, silica-zirconia, silica-titania, silica-titania-barium oxide, silica-titania-zirconia, quartz, alumina, titania, zirconia, and glass can be used. In addition, it is preferable that these inorganic oxide particles are fired at high temperatures to make them dense. In addition, in order to improve the densification effect by high-temperature sintering, a small amount of an oxide of a metal of Group I of the periodic table, such as sodium, may be contained. In addition, if necessary, a cation-eluting inorganic filler known as a dental inorganic filler, such as silicate glass or fluoroaluminosilicate glass, or a metal fluoride, such as ytterbium trifluoride, may be blended.

[0043] Among these inorganic oxide particles, silica-based composite oxide particles are particularly preferred because they have an easy refractive index adjustment and a large number of silanol groups on the surface, making it easy to perform surface modification with a silane coupling agent or the like. In addition, silica-zirconia, silica-titania, and silica-titania-barium oxide are preferred because they have strong X-ray contrast properties. Furthermore, silica-zirconia is the most preferred because it can produce a cured product with better wear resistance.

[0044] These inorganic oxide particles may be produced by any method, such as a wet method, a dry method, a sol-gel method, etc. Among them, the sol-gel method is preferable because it is advantageous for industrially producing fine particles having a spherical shape and excellent monodispersity, and it is also easy to adjust the refractive index and provide X-ray contrast properties.

[0045] The refractive index of the inorganic particles is not particularly limited, and inorganic particles having a refractive index in the range of 1.4 to 1.7, which is the refractive index of inorganic fillers used as fillers in conventional dental hardenable compositions, can be used. The inorganic particles are preferably treated with a surface treatment agent, typically a silane coupling agent, from the viewpoint of improving compatibility with the polymerizable monomer (a) and improving mechanical strength and water resistance.

[0046] Methods for producing spherical composite inorganic oxide particles by the sol-gel method are known, for example, from JP-A-58-110414, JP-A-58-151321, JP-A-58-156524, and JP-A-58-156526.

[0047] 1-3. Manufacturing method of organic-inorganic composite filler The method for producing the organic-inorganic composite filler of the present invention will be described below. As described above, there is a method disclosed in Patent Document 3 as a method for producing a microporous organic-inorganic non-composite filler, but the shape of the microporous organic-inorganic non-composite filler produced by this method is approximately spherical, and it is difficult to produce the organic-inorganic composite filler of the present invention by this method. In contrast, the production method of the present invention makes it possible to efficiently produce the organic-inorganic composite filler of the present invention.

[0048] The production method of the present invention is characterized by including the following steps (1) to (4).

[0049] (1) a slurrying step of mixing inorganic particles (B) having an average primary particle size of 10 to 1,000 nm and a polymerizable monomer component (a) in the presence of an organic solvent such that the ratio of the mass of the inorganic particles to the total mass of both is 80 to 95 mass % to obtain a slurry in which components insoluble in the organic solvent are uniformly dispersed; (2) a drying step of removing the organic solvent from the slurry to obtain an agglomerated mass consisting of a mixture of the polymerizable monomer component (a) and the inorganic particles (B); (3) a curing step of polymerizing and curing the polymerizable monomer component (a) contained in the aggregates to obtain an aggregated microporous body comprising a composite of the organic resin component (A) and the inorganic particles (B) which is a cured product of the polymerizable monomer (a); and (4) A grinding step for grinding the aggregated microporous body into powder.

[0050] As the inorganic particles (B) and the polymerizable monomer component (a), those described in 1-1 and 1-2 are used. In addition, in order to polymerize and harden the polymerizable monomer component (a) in the curing step, an effective amount of a polymerization initiator is usually blended in the slurrying step. As the polymerization initiator, any of a photopolymerization initiator, a chemical polymerization initiator, and a thermal polymerization initiator can be used, but it is preferable to use a photopolymerization initiator or a thermal polymerization initiator because the timing of polymerization can be arbitrarily selected by external energy such as light or heat, and the manufacturing operation is simple. It is preferable to use a thermal polymerization initiator because it does not require any working environment such as under a light shield or under red light, and azo compounds such as azobisisobutyronitrile, which have high operational safety and little effect on coloring the organic-inorganic composite filler, are preferably used. The blending amount of the polymerization initiator is usually 0.1 to 5 parts by mass with respect to 100 parts by mass of the polymerizable monomer (a). In order to impart various functions to the organic-inorganic composite filler, additives such as ultraviolet absorbers, pigments, dyes, polymerization inhibitors, and fluorescent agents may be blended in the slurrying step.

[0051] In the slurrying step (1), for the reasons mentioned above, it is preferable to surface-treat the inorganic particles (B) with a silane coupling agent.Suitable silane coupling agents include methyltrimethoxysilane, methyltriethoxysilane, methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, vinyltrichlorosilane, vinyltriethoxysilane, vinyltris(β-methoxyethoxy)silane, γ-methacryloyloxypropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and hexamethyldisilazane.

[0052] The surface treatment method is not particularly limited, and known methods can be used without limitation. A typical treatment method is to disperse and mix inorganic particles and silane coupling agent in a suitable solvent using a ball mill or the like, and then dry using an evaporator or air drying. In addition, inorganic particles are uniformly dispersed in a volatile liquid medium such as water to form a slurry, to which a silane coupling agent is added, and the mixture is prepared into a fine mist by, for example, a high-speed air flow, and the mist is brought into contact with a high-temperature gas to volatilize the liquid medium, by spray drying, or the like.

[0053] The dried product (surface-treated inorganic particles) obtained by the surface treatment is usually dried by heating at 50°C to 150°C to completely remove the liquid medium such as water used for dispersion. In the production of the organic-inorganic composite filler of the present invention, it is preferable that the inorganic filler is dispersed in the slurrying step described below, since uniform pores can be formed. The temperature in the heat drying is preferably 50°C to 120°C, more preferably 50°C to 100°C, since the surface-treated inorganic particles are easily dispersed.

[0054] In the step (1), the inorganic particles (B) surface-treated as necessary and the polymerizable monomer (a) are mixed in a mixing ratio in which the mass ratio of the inorganic particles (B) to the total amount of the two is 80 to 95 mass%, preferably 82 to 93%, depending on the inorganic filling particle content of the target organic-inorganic composite filler, in the presence of an organic solvent to obtain a slurry in which the insoluble components are uniformly dispersed in the organic solvent. When the inorganic particles (B) are surface-treated with a silane coupling agent by the spray drying method and dried by heating at a temperature of 120°C or higher, they become roughly spherical aggregated particles, but by making the inorganic particles surface-treated and dried by heating under appropriate conditions into a uniform slurry in the presence of an organic solvent, the aggregated particles are broken down to make the individual inorganic particles (B) evenly contact and wet with the polymerizable monomer (a), and a homogeneous aggregated mass is obtained after the drying step. The organic solvent used in the slurrying step is not particularly limited, but methanol, ethanol, acetone, dichloromethane, etc. can be preferably used from the viewpoints of having high volatility that enables the time required for solvent removal to be shortened, being easily available and inexpensive, being highly safe for the human body during production, etc. The amount of the organic solvent used may be any amount that can obtain a uniform slurry, but it is preferably 20 to 500 parts by mass, particularly 30 to 100 parts by mass, relative to 100 parts by mass of the total mass of the inorganic particles (B) and the polymerizable monomer (a), because a uniform slurry can be obtained and drying can be performed efficiently.

[0055] Mixing for slurrying may be performed in one step or in multiple steps, but it is preferable to perform the mixing in two steps, namely, a first step in which inorganic particles (B) having an average primary particle size of 10 to 1000 nm and a polymerizable monomer component (a) are mixed so that the ratio of the mass of the inorganic particles to the total mass of the two is 80 to 95 mass%, to obtain a mixed powder consisting of a wet powder in which the polymerizable monomer component (a) is attached to the surface of the inorganic particles (B), and a second step in which the mixed powder and an organic solvent are mixed to obtain a slurry in which the insoluble components are uniformly dispersed in the organic solvent. At this time, it is preferable to use a mixing device for mixing in the first step from the viewpoint of uniformity. For example, a rocking mixer or a planetary mixer that mixes with a stirring blade can be used. In addition, as a mixing method in the second step, shaking stirring, ultrasonic stirring, or stirring and mixing using a kneader can be suitably adopted.

[0056] In the drying step (2), the organic solvent is removed from the slurry to obtain an aggregated mass consisting of a mixture of the polymerizable monomer component (a) and the inorganic particles (B). In this drying step, the individual particles of the inorganic particles (B) are mutually linked with the polymerizable monomer component (a) as a binder to form an aggregated mass, and pores (open to the outside) are formed between the particles. The organic solvent is preferably removed until substantially the entire amount (usually 95% by mass or more) of the organic solvent is removed and a visually lumpy solid is obtained. The method for removing the organic solvent is not particularly limited as long as it is capable of such removal, but from the viewpoint of the desired pore formation, it is preferably performed by reduced pressure drying (or vacuum drying) in which drying is performed under a reduced pressure of 0.01 to 50 hectopascals, particularly 0.1 to 10 hectopascals.

[0057] The polymerization and curing in the curing step (3) may be carried out by appropriately selecting a suitable method depending on the type of polymerization initiator used. The polymerized and cured product (microporous aggregate) obtained by the polymerization and curing is pulverized in the pulverization step (4) to produce the organic-inorganic composite filler of the present invention. The pulverization can be carried out using a vibration ball mill, a bead mill, a jet mill, or the like. As described above, the average particle size of the porous organic-inorganic composite particles constituting the organic-inorganic composite filler of the present invention is preferably 5 to 100 μm, more preferably 10 to 100 μm, even more preferably 10 to 70 μm, and the proportion of fine particles having a particle size of 5 μm or less is less than 15% by volume, particularly less than 10% by volume, because the filling rate of the filler that can be blended in the dental curable composition is not reduced and better paste properties can be obtained more reliably. (4) The content of inorganic particles (B) in the porous organic-inorganic composite particles constituting the organic-inorganic composite filler is preferably 80 to 90% by mass, particularly 82 to 88% by mass, because particles having an average particle size of less than 5 μm are unlikely to be generated due to crushing in the grinding process and the average particle size can be easily and efficiently controlled to a range of 10 to 100 μm, particularly 10 to 70 μm.

[0058] In the manufacturing method of the present invention, in order to control the particle size distribution of the organic-inorganic composite filler of the present invention to the above-mentioned After the pulverization step (4), classification is performed so that the average particle size, which is the median size in a volume-based particle size distribution, is 10 to 100 μm and the proportion of fine particles in the particle size distribution is less than 15%. Further includes a classification process 。 It is possible to obtain such a particle size distribution by controlling the grinding conditions in the grinding step (4). However, to reliably obtain such a particle size distribution, fine particles with a particle diameter of 5 μm or less are required. Remove and It is preferable to remove coarse particles having a particle size much larger than 100 μm. Classification can be carried out using a sieve, an air classifier, a water classifier, or the like.

[0059] The organic-inorganic composite filler of the present invention may be subjected to a surface treatment, which imparts higher mechanical strength to a hardened product of a dental hardenable composition containing the organic-inorganic composite filler. The surface treatment agent and the surface treatment method used are the same as those for the surface treatment of the inorganic particles described above.

[0060] 2. Dental hardenable composition of the present invention As already described, the organic-inorganic composite filler of the present invention is particularly useful as a dental filler to be blended in a dental hardenable composition. In addition to the organic-inorganic composite filler, a polymerizable monomer and a polymerization initiator are blended in the dental hardenable composition of the present invention.

[0061] As the polymerizable monomer, any one used for the purpose can be used without any restrictions. Usually, it is sufficient to select from the same category of polymerizable monomers exemplified for the production of the organic-inorganic composite filler described above. The blending amount of the polymerizable monomer is 10 to 100 parts by mass, preferably 20 to 80 parts by mass, per 100 parts by mass of the organic-inorganic composite filler.

[0062] As the polymerization initiator, those used for the purpose can be used without any restrictions. For example, the thermal polymerization initiators exemplified for polymerizing and curing the polymerizable monomer blended in the organic composite filler can be used. In general, photopolymerization is often adopted as a means for curing (polymerizing) dental curable compositions because of the ease of operation during use. For the above reasons, it is preferable to use a photopolymerization initiator as a polymerization initiator in the dental curable composition of the present invention.

[0063] Examples of preferred photopolymerization initiators include benzoin alkyl ethers, benzil ketals, benzophenones, α-diketones, thioxanthone compounds, and bisacylphosphine oxides. A reducing agent is often added to the photopolymerization initiator. Examples of the reducing agent include aromatic amines, aliphatic amines, aldehydes, and sulfur-containing compounds. Furthermore, trihalomethyltriazine compounds, aryl iodonium salts, and the like can be added as necessary. The polymerization initiator is generally blended in the range of 0.01 to 10 parts by mass with respect to 100 parts by mass of the polymerizable monomer.

[0064] Other inorganic fillers can be added to the dental hardenable composition as long as the effect of the present invention is not impaired. As the other inorganic fillers, known fillers used for the purpose can be used without limitation. For example, the other inorganic fillers can include inorganic particles of the same material as the inorganic particles.

[0065] Furthermore, the dental hardenable composition of the present invention may contain known additives, such as polymerization inhibitors, pigments, ultraviolet absorbers, fluorescent agents, etc., within the limits of not significantly impairing the effects of the composition.

[0066] The dental hardenable composition of the present invention can be generally produced by thoroughly kneading the above-mentioned essential components and the optional components added as necessary in a predetermined amount to obtain a paste, and then degassing the paste under reduced pressure to remove air bubbles. The dental hardenable composition is not particularly limited in its application, but a particularly suitable application is a dental composite restorative material such as a dental filling and restorative material or a dental indirect restorative material. EXAMPLES

[0067] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0068] 1. Raw materials and their abbreviations The various raw materials used in the examples and comparative examples and their abbreviations are shown below.

[0069] (1) Polymerizable monomer 3G: Triethylene glycol dimethacrylate GMA: 2,2-bis[(3-methacryloyloxy-2-hydroxypropyloxy)phenyl]propane UDMA: 1,6-bis(methacrylethyloxycarbonylamino)-2,2-4-trimethylhexane · HD: 1,6-Hexanediol dimethacrylate.

[0070] (2) Inorganic particles F-1: Spherical silica-zirconia particles produced by the sol-gel method (average particle size of primary particles: 200 nm, average uniformity of primary particles: 0.95) F-2: Spherical silica-zirconia particles produced by the sol-gel method (average particle size of primary particles: 400 nm, average uniformity of primary particles: 0.95) F-3: Silica-titania particles produced by the sol-gel method (average particle size of primary particles: 70 nm, average uniformity of primary particles: 0.95) F-4: Irregular silica-zirconia particles produced by the sol-gel method (average particle size of primary particles: 1000 nm) F-5: Spherical ytterbium trifluoride particles (average particle size of primary particles: 50 nm) The average particle size and average uniformity of the primary particles are values ​​measured by the measurement method shown in (4) below.

[0071] (3) Polymerization initiator AIBN: Azobisisobutyronitrile CQ: Camphorquinone ·DMBE: Ethyl N,N-dimethyl-p-benzoate.

[0072] (4) Measurement method for average primary particle size and average uniformity of inorganic particles Photographs of the powder were taken at magnifications of 5,000 to 100,000 times using a scanning electron microscope (Philips, "XL-30S"), and the photographed images were processed using image analysis software ("IP-1000PC", product name; Asahi Kasei Engineering Corporation). The number of particles observed within a unit field of view of the photograph (30 or more) and the primary particle diameter (maximum diameter) were measured, and the number average particle diameter was calculated based on the measured values ​​using the following formula.

[0073]

number

[0074] In addition, for the particles observed within a unit field of view, the number (n: 30 or more), the maximum diameter of the particle (long diameter (Li)), and the diameter in the direction perpendicular to the long diameter (Bi) were obtained, and the average uniformity of the inorganic filler was calculated using the following formula.

[0075]

number

[0076] 2. Examples and Comparative Examples of Organic-Inorganic Composite Filler and Its Manufacturing Method (2.1) Examples 1 to 12 and Comparative Examples 1 to 5 In these Examples and Comparative Examples, the proportion of fine particles was not measured, and therefore Examples 1 to 12 are only reference examples. Example 1 Slurrying process: Surface treatment of inorganic particles: 100 g of inorganic filler F-1 was added to 200 g of water, and a dispersion liquid in which the inorganic filler was dispersed was obtained using a circulation type grinder SC mill. Next, γ-methacryloyloxypropyltrimethoxysilane and acetic acid were added to water and stirred to obtain a uniform solution with a pH of 4. This solution was added to the inorganic particle dispersion liquid and mixed uniformly. Then, while mixing the dispersion liquid, it was supplied onto a disk rotating at high speed and dried by a spray drying method. The spray drying was performed using a spray dryer (spray dryer "TSR-2W", manufactured by Sakamoto Giken Co., Ltd.) equipped with a rotating disk and atomizing by centrifugal force, with the disk rotation speed: 10000 rpm and spray drying temperature: 200 ° C. Then, the spray-dried inorganic powder was vacuum dried at 80 ° C. for 18 hours. First step: To 90 g of the obtained powder (inorganic agglomerated particles), a polymerizable monomer mixture was added, which was prepared by previously mixing 6.0 g of GMA as polymerizable monomers, 4.0 g of 3G, and 0.04 g of AIBN as a polymerization initiator, and the mixture was mixed for 30 minutes using a planetary mixer (manufactured by Inoue Seisakusho) with the stirring blade rotating at 7 to 10 rpm to obtain a mixed powder. Second step: 40 g of ethanol was added as an organic solvent to the above mixed powder, and further mixed to obtain a homogeneous slurry with high fluidity. Drying, curing and grinding process: The slurry was vacuum-dried at 25°C using a vacuum dryer, and the ethanol was removed by distillation. The mixture was then heated at 100°C for 2 hours using a vacuum dryer to polymerize and harden the polymerizable monomer, resulting in a cake-like white solid. The hardened product was then pulverized using a vibration ball mill (zirconia ball diameter: 5 mm), and the pulverized product was sieved to remove particles of 100 μm or more.

[0077] When the shape of each particle constituting the organic-inorganic composite filler thus obtained was observed visually (by a scanning electron microscope), it was found to have an irregular shape with edges characteristic of crushed material. Furthermore, when the average particle diameter, the cumulative pore volume and the average pore diameter in the range of 1 to 500 nm were measured by the method described below, the average particle diameter was 37 μm and the cumulative pore volume was 0.15 cm 2 / g and the average pore size was 62 nm.

[0078] (1) Method for measuring the average particle size of organic-inorganic composite fillers 0.1g of organic-inorganic composite filler was dispersed in 10ml of ethanol and irradiated with ultrasonic waves for 20 minutes. The median diameter of the volume statistics was calculated using a particle size distribution analyzer (LS230, Beckman Coulter) using the laser diffraction-scattering method and the optical model "Fraunhofer".

[0079] (2) Method for measuring pore volume and average pore diameter of organic-inorganic composite filler 0.1 g of organic-inorganic composite filler was placed in a sample cell, and pretreatment was performed by evacuation at 120°C for 3 hours using a pretreatment device ("VacuPrep 061" manufactured by Shimadzu Corporation). After that, nitrogen adsorption isotherm was obtained using a gas adsorption pore distribution measurement device ("Tristar II3020" manufactured by Shimadzu Corporation) using nitrogen as the adsorption gas and liquid nitrogen as the refrigerant, and the cumulative pore volume in the pore diameter range of 1 to 500 nm was obtained by the BJH method. In addition, the average pore diameter was calculated from the pore volume and the specific surface area calculated by the BET method.

[0080] Examples 2 to 9 The organic-inorganic composite filler was obtained in the same manner as in Example 1, except that the type of inorganic filler, the type of polymerizable monomer component, and the blending amount of the inorganic filler and the polymerizable monomer component were changed as shown in Table 1, and each physical property was measured for each of the organic-inorganic composite fillers in the same manner as in Example 1. The results are also shown in Table 1.

[0081] Example 10 76 g of inorganic aggregated particles F-1 surface-treated with γ-methacryloyloxypropyltrimethoxysilane obtained in the same manner as in Example 1 and 19 g of inorganic filler F-5 were mixed with 4.0 g of UDMA as a polymerizable monomer, 1.0 g of HD, and 0.02 g of AIBN as a polymerization initiator to prepare a polymerizable monomer mixture, which was then mixed for 30 minutes at a rotation speed of 7 to 10 rpm using a planetary mixer (manufactured by Inoue Seisakusho) to obtain a mixed powder. 40 g of ethanol was added as an organic solvent to the above mixed powder, and further mixed to obtain a uniform slurry with high fluidity. The above slurry was vacuum-dried at 25°C using a vacuum dryer, and after the ethanol was distilled off, it was heated at 100°C using a vacuum dryer for 2 hours to polymerize and harden the polymerizable monomer, thereby obtaining a cake-like white solid. Next, this hardened material was pulverized in a vibration ball mill (zirconia ball diameter: 5 mm), and the pulverized material was sieved to remove particles of 100 μm or more. The average particle size of the resulting crushed organic-inorganic composite filler was 35 μm, and the cumulative pore volume in the range of 1 to 500 nm determined by the nitrogen adsorption method was 0.09 cm 2 / g, and the average pore diameter was 35 nm.

[0082] Examples 11 and 12 Except for changing the type of inorganic filler and the amount of inorganic filler and polymerizable monomer component to be mixed in the organic-inorganic composite filler as shown in Table 1, organic-inorganic composite fillers were obtained in the same manner as in Example 10, and the physical properties of each were measured in the same manner as in Example 1. The results are also shown in Table 1.

[0083] Comparative Example 1 To 75 g of inorganic aggregated particles of F-1 surface-treated with the same γ-methacryloyloxypropyltrimethoxysilane as in Example 1, 15.0 g of GMA as a polymerizable monomer, 10.0 g of 3G, and 0.10 g of AIBN as a polymerization initiator were mixed in advance to prepare a polymerizable monomer mixture, which was then mixed for 30 minutes at a stirring blade rotation speed of 7 to 10 rpm using a planetary mixer (manufactured by Inoue Seisakusho) to prepare a paste-like mixture. This paste-like mixture was degassed under reduced pressure and then polymerized and cured at 100°C for 2 hours. The cured product was pulverized with a vibration ball mill (zirconia ball diameter: 5 mm), and the pulverized product was sieved to remove particles of 100 μm or more. The obtained organic-inorganic composite filler was amorphous, had an average particle size of 45 μm, and no pores were confirmed by measurement using a nitrogen adsorption method.

[0084] Comparative Example 2 The amounts of inorganic filler and polymerizable monomer components to be mixed in the organic-inorganic composite filler were changed as shown in Table 1, but the organic-inorganic composite filler was obtained in the same manner as in Comparative Example 1, and each physical property was measured in the same manner as in Example 1. The results are also shown in Table 1.

[0085] Comparative Example 3 100g of inorganic filler F-1 was added to 200g of water, and a dispersion liquid in which the inorganic filler was dispersed was obtained using a circulation type grinder SC mill. Next, γ-methacryloyloxypropyltrimethoxysilane and acetic acid were added to water and stirred to obtain a uniform solution with a pH of 4. This solution was added to the inorganic particle dispersion liquid and mixed uniformly. Then, using a spray dryer (spray dryer "NL-5", manufactured by Okawara Kakoki Co., Ltd.) that mixes the dispersion liquid while colliding with particulate air at the nozzle tip to form fine particles, the spray pressure was set to 0.08MPa, the drying temperature was set to 230°C, and the mixture was dried by spray drying. The spray-dried inorganic powder was then vacuum-dried at 120°C for 18 hours to obtain inorganic aggregated particles. Next, 80 g of the inorganic aggregated particles were immersed in a polymerizable monomer solution prepared by mixing 12.0 g of GMA as a polymerizable monomer, 8.0 g of 3G, 0.08 g of AIBN as a polymerization initiator, and 80 g of ethanol as an organic solvent. The mixture was thoroughly stirred, and after it was confirmed that the mixture had become a slurry, it was left to stand for 1 hour. The above mixture was dried for 1 hour under conditions of a vacuum of 10 hectopascals and heating at 40°C (using a hot water bath) while stirring in a rotary evaporator to remove the organic solvent. A smooth powder was obtained by removing the organic solvent. The powder was heated for 2 hours under conditions of a vacuum degree of 10 hectopascals and heating conditions of 100°C (using an oil bath) while stirring in a rotary evaporator, and the polymerizable monomer in the powder was polymerized and cured. The obtained organic-inorganic composite filler was approximately spherical, had an average particle diameter of 20 μm, and an integrated pore volume in the range of 1 to 500 nm determined by a nitrogen adsorption method of 0.04 cm. 2 / g, and the average pore diameter was 48 nm.

[0086] Comparative Example 4 An organic-inorganic composite filler was obtained in the same manner as in Comparative Example 3, except that the blending amounts of the inorganic filler and the polymerizable monomer component blended in the organic-inorganic composite filler were changed as shown in Table 1. The obtained organic-inorganic composite filler was approximately spherical, had an average particle size of 20 μm, and an integrated pore volume in the range of 1 to 500 nm determined by a nitrogen adsorption method of 0.09 cm. 2 / g, and the average pore diameter was 55 nm.

[0087] Comparative Example 5 100g of inorganic filler F-1 was added to 200g of water, and a dispersion liquid in which the inorganic filler was dispersed was obtained using a circulation type grinder SC mill. Next, γ-methacryloyloxypropyltrimethoxysilane and acetic acid were added to water and stirred to obtain a uniform solution with a pH of 4. This solution was added to the inorganic particle dispersion liquid and mixed uniformly. Then, while mixing the dispersion liquid, it was supplied onto a disk rotating at high speed and dried by a spray drying method. The spray dryer used was a spray dryer equipped with a rotating disk and atomized by centrifugal force (spray dryer "TSR-2W", manufactured by Sakamoto Giken Co., Ltd.). The rotation speed of the disk was 10000 rpm, and the spray drying temperature was 200 ° C. Then, the spray-dried inorganic powder was vacuum dried at 120 ° C for 18 hours to obtain inorganic aggregated particles. Next, 80 g of the inorganic aggregated particles were immersed in a polymerizable monomer solution prepared by mixing 12.0 g of GMA as a polymerizable monomer, 8.0 g of 3G, 0.08 g of AIBN as a polymerization initiator, and 80 g of ethanol as an organic solvent. The mixture was thoroughly stirred, and after it was confirmed that the mixture had become a slurry, it was left to stand for 1 hour. The above mixture was dried for 1 hour under conditions of a vacuum of 10 hectopascals and heating at 40°C (using a hot water bath) while stirring in a rotary evaporator to remove the organic solvent. A smooth powder was obtained by removing the organic solvent. The powder was heated for 2 hours under conditions of a vacuum degree of 10 hectopascals and heating conditions of 100°C (using an oil bath) while stirring in a rotary evaporator, and the polymerizable monomer in the powder was polymerized and cured. The obtained organic-inorganic composite filler was approximately spherical, had an average particle size of 50 μm, and an integrated pore volume in the range of 1 to 500 nm determined by a nitrogen adsorption method of 0.04 cm. 2 / g, and the average pore diameter was 50 nm.

[0088] [Table 1]

[0089] (2.2) Examples 13 to 22 and Comparative Examples 6 to 10 Example 13 A cake-like white solid was obtained in the same manner as in Example 3 with respect to the type of inorganic filler to be blended in the organic-inorganic composite filler, the type of polymerizable monomer component, the blending amount of the inorganic filler and the polymerizable monomer component, and the slurrying process, drying process, and hardening process in the manufacturing process. The hardened product obtained was then pulverized in a vibration ball mill (zirconia ball diameter: 5 mm) for 30 minutes, and the pulverized product was sieved with a 100 μm mesh to remove particles of 100 μm or more. The average particle diameter of the obtained crushed organic-inorganic composite filler, the cumulative pore volume and the average pore diameter obtained by the nitrogen adsorption method were measured, and the volumetric proportion (fine particle presence proportion) was obtained for the range of 0.04 μm to 5.0 μm from the particle size distribution obtained during the average particle diameter (particle size) measurement. As a result, the average particle diameter was 48 μm, the volumetric proportion of particles of 5 μm or less in the particle size distribution was 7.6%, and the cumulative pore volume was 0.09 cm 2 / g and the average pore size was 40 nm.

[0090] Example 14 A cake-like white solid was obtained in the same manner as in Example 13, with respect to the type of inorganic filler to be blended in the organic-inorganic composite filler, the type of polymerizable monomer component, the blending amount of the inorganic filler and the polymerizable monomer component, and the slurrying step, drying step, and hardening step in the manufacturing process. Next, this hardened material was pulverized in a vibration ball mill (zirconia ball diameter: 5 mm) for 60 minutes, and the pulverized material was sieved with a 100 μm mesh to remove particles of 100 μm or more. The physical properties of the obtained crushed organic-inorganic composite filler were measured in the same manner as in Example 13. As a result, the average particle size was 40 μm, the volumetric ratio of particles of 5 μm or less in the particle size distribution was 11.7%, and the cumulative pore volume was 0.10 cm 2 / g and the average pore size was 40 nm.

[0091] Example 15 The organic-inorganic composite filler obtained in Example 13 was passed through a sieve with 10 μm openings, and the components remaining on the sieve were collected to remove fine particles. The obtained crushed organic-inorganic composite filler was measured for various physical properties in the same manner as in Example 1. As a result, the average particle size was 51 μm, the volumetric proportion of particles of 5 μm or less in the particle size distribution was 2.0%, and the cumulative pore volume was 0.08 cm 2 / g and the average pore size was 40 nm.

[0092] Examples 16 to 20 The organic-inorganic composite filler was obtained in the same manner as in Example 13, except that the type of inorganic filler, the type of polymerizable monomer component, and the amount of inorganic filler and polymerizable monomer component were changed as shown in Table 2, and each physical property was measured in the same manner as in Example 213. The results are also shown in Table 2.

[0093] Example 21 72 g of inorganic aggregated particles F-1 surface-treated with γ-methacryloyloxypropyltrimethoxysilane obtained in the same manner as in Example 13, and 18 g of inorganic filler F-5 were mixed with 8.0 g of UDMA as a polymerizable monomer, 2.0 g of HD, and 0.04 g of AIBN as a polymerization initiator to prepare a polymerizable monomer mixture, which was then mixed for 30 minutes at a stirring blade rotation speed of 7 to 10 rpm using a planetary mixer (manufactured by Inoue Seisakusho) to obtain a mixed powder. 40 g of ethanol was added as an organic solvent to the above mixed powder, and further mixed to obtain a uniform slurry with high fluidity. The above slurry was vacuum-dried at 25°C using a vacuum dryer, and after the ethanol was distilled off, it was heated at 100°C using a vacuum dryer for 2 hours to polymerize and harden the polymerizable monomer, thereby obtaining a cake-like white solid. Next, this cured product was pulverized in a vibration ball mill (zirconia ball diameter: 5 mm) for 30 minutes, and the pulverized product was sieved through a 100 μm mesh sieve to remove particles of 100 μm or more. The obtained crushed organic-inorganic composite filler was measured for each physical property in the same manner as in Example 13. The average particle size was 42 μm, the volumetric proportion of particles of 5 μm or less in the particle size distribution was 2.0%, and the cumulative pore volume was 0.05 cm. 2 / g and the average pore size was 30 nm.

[0094] Example 22 The type of inorganic filler to be mixed in the organic-inorganic composite filler, the type of polymerizable monomer component, the mixing amount of the inorganic filler and the polymerizable monomer component, and the slurrying step, drying step, and hardening step in the manufacturing process were the same as in Example 13, and a cake-like white solid was obtained. Next, this hardened material was pulverized for 120 minutes in a vibration ball mill (zirconia ball diameter: 5 mm), and the pulverized material was passed through a sieve with an opening of 100 μm to remove particles of 100 μm or more. The obtained crushed organic-inorganic composite filler :CF-27 The physical properties of the powder were measured in the same manner as in Example 13. As a result, the average particle size was 37 μm, and the volume ratio of particles having a size of 5 μm or less in the particle size distribution was 1.0 μm. (Fine particle content) is 20.2%, and the cumulative pore volume is 0.09 cm 2 / g and the average pore size was 37 nm. In addition, this example corresponds to a comparative example since the proportion of fine particles is 15% or more.

[0095] Comparative Example 6 To 75 g of inorganic aggregated particles of F-1 surface-treated with the same γ-methacryloyloxypropyltrimethoxysilane as in Example 13, 15.0 g of GMA as a polymerizable monomer, 10.0 g of 3G, and 0.10 g of AIBN as a polymerization initiator were mixed in advance to prepare a polymerizable monomer mixture, which was then mixed for 30 minutes at a stirring blade rotation speed of 7 to 10 rpm using a planetary mixer (manufactured by Inoue Seisakusho) to prepare a paste-like mixture. This paste-like mixture was degassed under reduced pressure and then polymerized and cured at 100°C for 2 hours. The cured product was pulverized for 30 hours with a vibration ball mill (zirconia ball diameter: 5 mm), and the pulverized product was sieved to remove particles of 100 μm or more. The obtained organic-inorganic composite filler was amorphous, had an average particle size of 45 μm, and the volumetric ratio of particles of 5 μm or less in the particle size distribution was 7.5%, and no pores were confirmed in the measurement by nitrogen adsorption method.

[0096] Comparative Example 7 The amounts of inorganic filler and polymerizable monomer components to be mixed in the organic-inorganic composite filler were changed as shown in Table 3, but the organic-inorganic composite filler was obtained in the same manner as in Comparative Example 6, and each physical property was measured in the same manner as in Example 13. The results are also shown in Table 2.

[0097] Comparative Example 8 100g of inorganic filler F-1 was added to 200g of water, and a dispersion liquid in which the inorganic filler was dispersed was obtained using a circulation type grinder SC mill. Next, γ-methacryloyloxypropyltrimethoxysilane and acetic acid were added to water and stirred to obtain a uniform solution with a pH of 4. This solution was added to the inorganic particle dispersion liquid and mixed uniformly. Then, using a spray dryer (spray dryer "NL-5", manufactured by Okawara Kakoki Co., Ltd.) that mixes the dispersion liquid while colliding with particulate air at the nozzle tip to form fine particles, the spray pressure was set to 0.08MPa, the drying temperature was set to 230°C, and the mixture was dried by spray drying. The spray-dried inorganic powder was then vacuum-dried at 120°C for 18 hours to obtain inorganic aggregated particles. Next, 80 g of the inorganic aggregated particles were immersed in a polymerizable monomer solution prepared by mixing 12.0 g of GMA as a polymerizable monomer, 8.0 g of 3G, 0.08 g of AIBN as a polymerization initiator, and 80 g of ethanol as an organic solvent. The mixture was thoroughly stirred, and after it was confirmed that the mixture had become a slurry, it was left to stand for 1 hour. The above mixture was dried for 1 hour under conditions of a vacuum of 10 hectopascals and heating at 40°C (using a hot water bath) while stirring in a rotary evaporator to remove the organic solvent. A smooth powder was obtained by removing the organic solvent. The powder was heated for 2 hours under conditions of a vacuum degree of 10 hectopascals and heating conditions of 100°C (using an oil bath) while stirring in a rotary evaporator, and the polymerizable monomer in the powder was polymerized and cured. The obtained organic-inorganic composite filler was approximately spherical, had an average particle size of 20 μm, and no particles of 5 μm or less were confirmed in the particle size distribution. The cumulative pore volume in the range of 1 to 500 nm determined by the nitrogen adsorption method was 0.04 cm. 2 / g, and the average pore diameter was 48 nm.

[0098] Comparative Example 9 An organic-inorganic composite filler was obtained in the same manner as in Comparative Example 19, except that the blending amounts of the inorganic filler and the polymerizable monomer component blended in the organic-inorganic composite filler were changed as shown in Table 2. The obtained organic-inorganic composite filler was approximately spherical, had an average particle size of 20 μm, and no particles of 5 μm or less were observed in the particle size distribution. The cumulative pore volume in the range of 1 to 500 nm determined by the nitrogen adsorption method was 0.09 cm. 2 / g, and the average pore diameter was 55 nm.

[0099] Comparative Example 10 100g of inorganic filler F-1 was added to 200g of water, and a dispersion liquid in which the inorganic filler was dispersed was obtained using a circulation type grinder SC mill. Next, γ-methacryloyloxypropyltrimethoxysilane and acetic acid were added to water and stirred to obtain a uniform solution with a pH of 4. This solution was added to the inorganic particle dispersion liquid and mixed uniformly. Then, while mixing the dispersion liquid, it was supplied onto a disk rotating at high speed and dried by a spray drying method. The spray dryer used was a spray dryer equipped with a rotating disk and atomized by centrifugal force (spray dryer "TSR-2W", manufactured by Sakamoto Giken Co., Ltd.). The rotation speed of the disk was 10000 rpm, and the spray drying temperature was 200 ° C. Then, the spray-dried inorganic powder was vacuum dried at 120 ° C for 18 hours to obtain inorganic aggregated particles. Next, 80 g of the inorganic aggregated particles were immersed in a polymerizable monomer solution prepared by mixing 12.0 g of GMA as a polymerizable monomer, 8.0 g of 3G, 0.08 g of AIBN as a polymerization initiator, and 80 g of ethanol as an organic solvent. The mixture was thoroughly stirred, and after it was confirmed that the mixture had become a slurry, it was left to stand for 1 hour. The above mixture was dried for 1 hour under conditions of a vacuum of 10 hectopascals and heating at 40°C (using a hot water bath) while stirring in a rotary evaporator to remove the organic solvent. A smooth powder was obtained by removing the organic solvent. The powder was heated for 2 hours under conditions of a vacuum degree of 10 hectopascals and heating conditions of 100°C (using an oil bath) while stirring in a rotary evaporator, and the polymerizable monomer in the powder was polymerized and cured. The obtained organic-inorganic composite filler was approximately spherical, had an average particle size of 50 μm, and no particles of 5 μm or less were confirmed in the particle size distribution. The cumulative pore volume in the range of 1 to 500 nm determined by the nitrogen adsorption method was 0.04 cm. 2 / g, and the average pore diameter was 50 nm.

[0100] [Table 2]

[0101] 3. Examples and Comparative Examples of Dental Curable Compositions (3.1) Examples 23 to 34 and Comparative Examples 11 to 15 The dental curable compositions of each example were prepared as follows using the organic / inorganic composite filler shown in Table 3. That is, 0.20 parts by mass of CQ and 0.35 parts by mass of DMBE were completely dissolved as a polymerization initiator in a polymerizable monomer consisting of 60 parts by mass of GMA and 40 parts by mass of 3G. Then, in a mortar, the obtained solution was mixed with 200 parts by mass of inorganic filler F-1 and 200 parts by mass of each organic / inorganic composite filler shown in Table 2 until uniform, and the mixture was degassed to prepare a paste-like dental curable composition of each example having a filler filling rate of 80% by mass. In addition, Examples 23 to 34 are reference examples since they use organic-inorganic composite fillers for which the proportion of fine particles present has not been measured.

[0102] The obtained dental hardenable compositions were evaluated for handleability in a paste state, shape retention, and bending strength of the hardened product by the methods described below. The results are shown in Table 3.

[0103] (3.2) Examples 35 to 44 and Comparative Examples 16 to 20 The dental curable compositions of each example were prepared as follows using the organic / inorganic composite filler shown in Table 4. That is, 0.20 parts by mass of CQ and 0.35 parts by mass of DMBE were completely dissolved as a polymerization initiator in a polymerizable monomer consisting of 60 parts by mass of GMA and 40 parts by mass of 3G. Then, in a mortar, the obtained solution was mixed with 200 parts by mass of inorganic filler F-1 and 260 parts by mass of each organic / inorganic composite filler shown in Table 2 until uniform, and degassed to prepare the dental curable compositions of each example in the form of a paste, each with a filler filling rate of 82% by mass. In addition, Example 44 is an example corresponding to a comparative example since CF-27 obtained in Example 22, in which the content of fine particles is 15% or more, is used as the organic-inorganic composite filler.

[0104] The obtained dental hardenable compositions were evaluated for handleability in a paste state, shape retention, and bending strength of the hardened product by the methods described below. The results are shown in Table 4.

[0105] (1) Evaluation of the operability of the dental hardenable composition in a paste state The paste properties of the dental curable composition before hardening were evaluated based on the following criteria from the viewpoint of ease of handling. Those with little stickiness were rated as ○, those with particularly little stickiness were rated as ◎, and those with paste properties that were very sticky and difficult to handle were rated as ×. Furthermore, those with little roughness were rated as ○, those with particularly little stickiness were rated as ◎, and those with paste properties that were very rough and difficult to handle were rated as ×. The evaluation was performed immediately after the dental curable composition was prepared and after it was stored at 37°C for 6 months.

[0106] (2) Evaluation of paste shape retention The shape retention of the dental hardenable composition paste before hardening was evaluated by the following method. A hard resin tooth with a Class I cavity (diameter 4 mm, depth 2 mm) reproduced in the center of the occlusal surface of the lower right No. 6 was filled with the hardenable composition, and the occlusal surface shape was given to the filled paste. The hard resin tooth filled with the dental hardenable composition was then left to stand in an incubator at 50°C for 20 minutes, and it was evaluated whether the given shape was retained. Those that showed a slight change in the given shape were judged as ○, those that showed no change at all were judged as ◎, and those that could not retain the shape were judged as ×. The evaluation was performed immediately after the dental hardenable composition was prepared and after storing it at 37°C for 6 months.

[0107] (3) Evaluation of bending strength The dental hardenable composition paste was filled into a stainless steel mold using a filling device, and in a state of being pressed against polypropylene, light irradiation was performed from one side using a visible light irradiator Powerlight (manufactured by Tokuyama Corporation) for 30 seconds x 3 times, with the polypropylene being attached to the surface in different positions so that the light was irradiated from the other side in the same manner. Light irradiation was then performed for 30 seconds x 3 times to obtain a hardened body. The hardened body was trimmed into a 2 x 2 x 25 mm square column shape using #1500 waterproof abrasive paper, and this sample piece was attached to a testing machine (Shimadzu Corporation, Autograph AG5000D), and the three-point bending fracture strength was measured at a support distance of 20 mm and a crosshead speed of 1 mm / min. Five test pieces were evaluated, and the average value was taken as the bending strength. A load-deflection curve was obtained.

[0108] Formula: σ B=(3PS) / (2WB 2 ) The bending strength was calculated. The symbols in the above are, respectively, σ B : bending strength (Pa), P: load at the time of fracture of the test piece (N), S: distance between supports (m), W: width of the test piece (m), B: thickness of the test piece (m).

[0109] [Table 3]

[0110] [Table 4]

[0111] As shown in the results of Examples 23 to 44, the dental curable composition containing the organic-inorganic composite filler of the present invention exhibits high bending strength in the cured product, is less sticky in the paste state, and exhibits good shape retention. In addition, the change in operability and shape retention due to long-term storage is extremely small. Furthermore, according to the results of Examples 35 to 44, which evaluated the volumetric proportion of particles of 5 μm or less, when the above-mentioned proportion is small, such as 15% or less, the flakiness in the paste state is also small.

[0112] As shown in the results of Comparative Examples 11, 12, 16 and 17, dental curable compositions containing crushed organic-inorganic composite fillers with inorganic filler loading rates of 75% or less are less sticky in a paste state and have relatively good shape retention, but the bending strength of the cured product is low. In addition, after long-term storage, the paste properties are too rough and difficult to use.

[0113] As shown in the results of Comparative Examples 13 to 15 and 18 to 20, the dental hardenable compositions containing aggregated particle-type porous organic-inorganic composite fillers exhibited high bending strength in the hardened form, but were very sticky in the paste state and had a low ability to retain the applied shape.

Claims

1. The porous organic-inorganic composite particles are composed of a composite of an organic resin component (A) made of a cured product of a polymerizable monomer (a) and inorganic particles (B) having an average primary particle diameter of 10 to 1000 nm, and the cumulative pore volume of pores with a diameter of 1 to 500 nm measured by a nitrogen adsorption method is 0.01 to 0.30 cm 3 / g, The content of the inorganic particles (B) in the porous organic-inorganic composite particles is 80 to 95 mass %, Each of the porous organic-inorganic composite particles constituting the organic-inorganic composite filler has an irregular shape, The average particle size, which is the median size in a volume-based particle size distribution of the porous organic-inorganic composite particles constituting the organic-inorganic composite filler, measured by a laser diffraction-scattering method is 5 to 100 μm; and In the particle size distribution, the proportion of fine particles having a size of 5 μm or less is less than 15%. The organic-inorganic composite filler is characterized by the above-mentioned.

2. The organic-inorganic composite filler according to claim 1, wherein the content of the inorganic particles (B) in the porous organic-inorganic composite particles is 82 to 93 mass%, the average particle diameter of the porous organic-inorganic composite particles is 10 to 100 μm, and the presence ratio of fine particles having a size of 5 μm or less is less than 10% on a volume basis.

3. The individual porous organic-inorganic composite particles constituting the organic-inorganic composite filler have an irregular shape with edges, and the cumulative pore volume is 0.03 to 0.25 cm 3 The organic-inorganic composite filler according to claim 1 or 2, wherein the molecular weight is 1 / g.

4. The organic-inorganic composite filler according to claim 1 , wherein the inorganic particles (B) contain inorganic particles having X-ray contrast properties.

5. A method for producing the organic-inorganic composite filler according to claim 1, a slurrying step of mixing inorganic particles (B) having an average primary particle size of 10 to 1,000 nm and a polymerizable monomer component (a) in the presence of an organic solvent such that the ratio of the mass of the inorganic particles to the total mass of both is 80 to 95 mass % to obtain a slurry in which components insoluble in the organic solvent are uniformly dispersed; a drying step of removing the organic solvent from the slurry to obtain an agglomerated mass consisting of a mixture of the polymerizable monomer component (a) and the inorganic particles (B); a curing step of polymerizing and curing the polymerizable monomer component (a) contained in the aggregate to obtain an aggregate microporous body comprising a composite of the organic resin component (A) and the inorganic particles (B) which is a cured product of the polymerizable monomer (a); A grinding step of grinding the aggregated microporous body into powder; and a classification step of classifying the powder after the pulverization step so that the average particle size, which is the median size in a volume-based particle size distribution, is 10 to 100 μm and the proportion of fine particles having a size of 5 μm or less in the particle size distribution is less than 15%; The method according to claim 1, further comprising:

6. The method according to claim 5 , wherein the inorganic particles (B) mixed in the slurrying step are agglomerated particles of surface-treated primary particles, and the agglomerated particles are disintegrated by mixing in the coexistence of the organic solvent.

7. The slurrying step comprises: A first step of mixing inorganic particles (B) having an average primary particle size of 10 to 1000 nm with a polymerizable monomer component (a) such that the ratio of the mass of the inorganic particles to the total mass of the two is 80 to 95 mass %, thereby obtaining a mixed powder consisting of a wet powder in which the polymerizable monomer component (a) is attached to the surfaces of the inorganic particles (B); and A second step of mixing the mixed powder with an organic solvent to obtain a slurry in which the insoluble components are uniformly dispersed in the organic solvent. The method according to claim 5 or 6, comprising:

8. A dental hardenable composition comprising the organic-inorganic composite filler according to claim 1 , a polymerizable monomer, and a polymerization initiator.

Citation Information

Patent Citations

  • Restorative dental material composition

    JP2000080013A

  • Powder-liquid type dental photocurable material

    JP2014091688A

  • Dental hardening composition

    JP2015105254A

  • Organic inorganic composite filler, and curable composition containing the same

    JP2019183111A

  • Manufacturing method of polymerization curable composition

    JP2020090574A